Exploring Efl Students’ Descriptive Paragraph Writing Ability Through Critical Assessment Process - Ida Bagus Nyoman Mantra; Anak Agung Putu Arsana; I Gusti Ayu Putu Tuti Indrawati; Anak Agung Rai Laksmi (Denpasar Institute, 2021)
Writing is a visual depiction of thoughts, feelings, and ideas using the written language for communication purposes or conveying certain messages. Having the ability to write, of course, allows humans to communicate ideas, appreciation, and experiences to others. Writing skill is possessed through intensive training and guidance which must be trained continuously to gain excellent writing skill. This study explores EFL learners’ writing ability in actualizing their skill in writing a descriptive paragraph. The study revealed that EFL learners’ writing ability is under expected skill. Therefore, this study implies that intensive improvement programs should be conducted by the educational institution to maximize learners’ writing skills